The Effect of Leadership and Staff Competence on Staff Discipline at the Long Kali Subdistrict Office in Paser Regency - Husnia Hadijah; Syachrumsyah Asri; Agus Santosa (Journal of Social Research, 2026)
The purpose to be achieved in this study is to find out the influence of leadership and apparatus competence on apparatus discipline at the Long Kali District Office, Paser Regency. The research method used in this study is an explanatory survey. The research method used is an explanatory survey with a quantitative approach. The population consists of all 50 civil servants and non-civil servants at the Long Kali District Office, and the census method was employed, making the entire population the research sample. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The results showed that leadership has a significant effect on work discipline (Sig. 0.008), competence has a significant effect on work discipline (Sig. 0.000), and simultaneously both variables have a significant effect on work discipline (Sig. 0.000 < 0.05). The regression model has strong predictive power with an R Square value of 0.627, meaning that 62.7% of the variation in work discipline can be explained by leadership and competence. The regression equation formed is Work Discipline = -35.877 + 0.355(Competence) + 0.981(Leadership). Leadership has a more dominant influence on work discipline compared to competence. The study concludes that improving leadership effectiveness and apparatus competence simultaneously will significantly enhance work discipline at the sub-district office, which is essential for optimizing public services at the local government level.